Environmental Sustainability : An Evaluation of World Bank Group Support - Independent Evaluation Group (Washington, DC : World Bank, 2012)
The purpose of this evaluation is threefold. First, it seeks to assess how, and how well, the World Bank Group has supported its public and private sector clients in their efforts to achieve greater environmental sustainability over the past 15 years. Second, it attempts to identify the principal external and internal constraints on Bank Group effectiveness. And third, it seeks to suggest how some of these constraints, particularly the internal ones, can be reduced.